A Test of Some Principles In Information Campaign Planning - Rodolfo N. Salcedo; Hadley Read; James F. Evans; Ana C. Kong (Journal of Applied Communications, 1973)
ALTHOUGH INFORMATION campaigns are standard fare for agricultural colleges and the U. S. Department of Agriculture, the campaign reported here may be of special interest for at least three reasons.